A Study on the Potential of Gubug Payung Ecotourism Development in Blora Regency - Angestiwi, Tiafahmi; Rahman, Boby; Prihantini, P (Universitas Diponegoro, Indonesia, 2020)
Blora is one of the regencies with the lowest local revenue in the Central Java Province, this is very contrary to the potential of the region. One of the regional potentials which can be more developed is the natural tourism asset sector. Blora, with its extensive teak forest, even with one of the oldest teak trees and with an old train route for wood transportation, can be one of the attractions for tourists. The tourism asset sector is expected to increase revenue in Blora Regency. This study aims to generate potential asset development strategies for Gubug Payung ecotourism area as a source of regional revenue for Blora Regency. The research method used was quantitative rationalistic, with SWOT analysis technique approach. The data collection technique made use of interviews of relevant agencies in Blora Regency and the local community and literature reviews. Based on the baseline analysis, the potential asset development strategies of the Gubug Payung ecotourism area was carried out by supporting aggressive growth policies. Blora Regency requires an urban catalyst, so that it can reduce disparities between districts. Besides, the development of ecotourism assets can support the conservation of the dominant areas of protected teak forests.